Marrying for power: Gendered alliances in mafias - Maurizio Catino; Alberto Aziani; Sara Rocchi (PLoS ONE, 2026)
Drawing on judicial records documenting 770 inter-clan alliances through 906 marriages among 623 ’Ndrangheta clans, we analyze how matrimonial ties relate to power and cohesion within the organization. Powerful clans occupy central positions in the marriage network, while alliances among less influential clans function as critical “load-bearing” ties—whose simulated removal fragments the network most rapidly. Contrary to a “bride-receiving” narrative, we do not find clear evidence that status alone determines gendered exchange patterns; powerful clans’ higher share of incoming brides (0.559 versus 0.437) is not statistically significant. Instead, an inverted-U relationship emerges: clans with moderately high bride-receiving shares (≈55–60%) exhibit the highest centrality, whereas extreme senders or receivers are structurally peripheral. These findings are consistent with marriage operating as an organizational technology—where powerful families build overlapping ties to enhance resilience, and moderate gender asymmetries optimize both lineage consolidation and network brokerage. Overall, the ’Ndrangheta’s durability appears to depend as much on peripheral-to-peripheral alliances as on unions of powerful families, underscoring marriage’s dual role in maintaining cohesion and managing power.